2014
DOI: 10.1088/0022-3727/47/39/394017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of InAs/p–Si heterojunction nanowire-based solar cell

Abstract: The growth of compound semiconductor nanowires on the silicon platform has opened many new perspectives in the area of electronics, optoelectronics and photovoltaics. We have grown a 1 × 1 mm 2 array of InAs nanowires on p-type silicon for the fabrication of a solar cell. Even though the nanowires are spaced by a distance of 800 nm with a 3.3% filling volume, they absorb most of the incoming light resulting in an efficiency of 1.4%. Due to the unfavourable band alignment, carrier separation at the junction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Overall, these characteristics suggest that in the axial heterojunction geometry the passivated InAlAs-InGaAs core–shell NW structure acts as a low-loss carrier conductor and that most of the photocarriers are generated in the Si substrate. 58 This is further supported by measurements of the wavelength-dependent external quantum efficiency which indicate that that photocarrier generation by the NWs is negligible (see Supporting Information ).…”
mentioning
confidence: 63%
“…Overall, these characteristics suggest that in the axial heterojunction geometry the passivated InAlAs-InGaAs core–shell NW structure acts as a low-loss carrier conductor and that most of the photocarriers are generated in the Si substrate. 58 This is further supported by measurements of the wavelength-dependent external quantum efficiency which indicate that that photocarrier generation by the NWs is negligible (see Supporting Information ).…”
mentioning
confidence: 63%
“…19,20 The NWs were grown using a low-pressure (60 Torr) Emcore D-75 MOCVD system. Trimethylindium (TMIn), tertiarybutylarsine (TBAs), and tertiarybutylphosphine (TBP) were used as precursors, and hydrogen was used as a carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…And he experimentally concluded that enhanced In concentration could result in higher photocurrent up to 8.6% of illuminating light conversion. However, the power conversion efficiency (PCE) of InGaAs/InAs heterostructured nanowire array made by Parsion K. Mohseni can reach up to 2.51% [99] and solar cells made by InAs/p-Si heterojunction nanowire had a PCE of 1.4% [100]. In addition, Mallorqui further concluded that density and length reduction of nanowires could yield better performance [100].…”
Section: Characterization Of Nanowires For Photovoltaicsmentioning
confidence: 99%
“…However, the power conversion efficiency (PCE) of InGaAs/InAs heterostructured nanowire array made by Parsion K. Mohseni can reach up to 2.51% [99] and solar cells made by InAs/p-Si heterojunction nanowire had a PCE of 1.4% [100]. In addition, Mallorqui further concluded that density and length reduction of nanowires could yield better performance [100]. Considering the crucial importance of P/N junctions and hetero-junctions to application of solar cells, it is essential to understand the interfacial morphologies as well as elemental distributions on both sides of the junction, In this regards, APT has demonstrated unique advantages in studying P/N junctions and multi-layer study structure.…”
Section: Characterization Of Nanowires For Photovoltaicsmentioning
confidence: 99%